Improving the Thematic Learning Outcomes of Elementary School Through Make a Match Model With Question Box Media - Sri Budyartati; Endang Sri Maruti; Sumani; Wiwin Andriani (Studies in Learning and Teaching, 2023)
With the aid of the Question Box media and the Make a Match learning methodology, this study aimed to enhance theme learning results for class IV students. 11 pupils are the research subjects for this kind of classroom action research (CAR). Two cycles—cycle I and cycle II—of the research (CAR) were completed. The steps taken in this research's process are planning, carrying it out, observing it, and reflecting on it. Gathering information through testing, observation, and interviews. Data analysis with quantitative analysis by looking at data through test results. According to the study's findings utilizing the make-a-match model, the learning outcomes in the first cycle were on average 73, or 55% of the total, and in the second cycle, they were on average 92, or 91% of the total. The study's findings show that using box media with question can enhance theme learning outcomes because the application of the model to student learning outcomes has increased by 36%. Teachers can use a variety of models as learning innovations to give students learning motivation that can effect learning.